Metode Drilling: Transformasi Pembelajaran Keterampilan Berbicara Bahasa Inggris Bagi Siswa Kelas 6 di Desa Manggari Kec Lebakwangi Kab Kuningan: Transforming the Learning of English Speaking Skills for Grade 6 Students in Manggari Village, Lebakwangi District, Kuningan. - Azis, Ilham Ariffianto; Agustiana, Vina; Diani Rosa, Helfi; Cika Wandira, Inneke (Yayasan Kajian Riset dan Pengembangan RADISI, 2025)
This community service activity aimed to improve English speaking skills among children aged 10 to 12 years in Manggari Village, Lebakwangi District, Kuningan Regency. The training approach employed a drilling technique combined with role play, speech, and singing methods. Conducted in two face-to-face sessions, the program was designed to develop speaking habits through repetition, pronunciation, and contextual interaction. The results indicated a significant improvement in pronunciation, intonation, fluency, and participants' confidence. Moreover, students showed high enthusiasm toward the enjoyable and contextual learning process. Despite time constraints and challenges in mastering new vocabulary, the applied methods proved effective in creating an active and participatory learning atmosphere. This activity is expected to serve as an alternative model for communicative English instruction in community settings.